Suppose that the functions f and g are defined for all real numbers x as follows.

f(x)=4x^2

g(x)=2x

write the expression for (f*G)(x) and (f-g)9x) and evaluate (f+g)(-1)

f(x)=4x^{2}

write the expression for (f*g)(x) and (f-g)(x) and evaluate (f+g)(-1)

f(g(x)) = f(2x) = 4* (2x)^{2}= 16x^{2}

(f-g)(x) = f(x)-g(x) = 4x^{2} -2x

(f+g)(-1) = f(-1)+g(-1) = 4 *(-1)^{2}+2(-1) =4-2 =2

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up